Development Of Optimization Strategies For MSMES' Competitive Advantages In The Digital Era - Fathul Huda; Andhyka; Jenita Frisilia; Abdul Azis R; Rahmat Yanuary (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2025)
Maximizing digitalization is essential for MSMEs to thrive, requiring strategies that align with their business models. The digital era brings challenges, especially rising competition, necessitating precise approaches to sustain competitiveness. During the COVID-19 pandemic in 2021, Yeyadana Store adapted by adopting the 7P Marketing Mix, upgrading technology, and optimizing SEO content, which transformed its operations. MSMEs must adopt similar strategies to stay competitive and meet evolving customer expectations. This study examines factors affecting MSME competitiveness in Palu and suggests optimization strategies to support growth in the digital era. Employing a mixed-method approach, it begins with quantitative data collection and analysis, followed by qualitative validation. Findings reveal that only 36% of MSMEs in Palu use digital marketing, while 64% depend on traditional methods, emphasizing the need for wider digital adoption. Key strategies proposed include product and service development, customer data analysis, digital skill enhancement, social media marketing, and strategic partnerships.